Influence of cardiac phase on myocardial native T1 values by a segmental approach. (13th July 2021) - Pepe, A; Martini, N; Positano, V; D"angelo, G; Barison, A; Todiere, G; Grigoratos, C; Barra, V; Pistoia, L; Gargani, L; Ripoli, A; Meloni, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Native T1 values are usually assessed in the end-diastole to minimize motion artifacts while the systolic data acquisition offers the advantage of a thicker myocardium, with reduced partial-volume effects. Higher myocardial T1 values have been detected in diastole at both 1.5T and 3T but the dependence of this difference on myocardial segments or gender has not been fully explored. Aim. We provided a systematic comparison of myocardial native T1 values in diastole and systole, by considering separately myocardial segments and dividing males and females. Methods. Sixty-one healthy subjects (46.0 ± 14.1 years, 32 males) underwent CMR at 1.5T (Signa Artist; GE Healthcare). Three short-axis slices of the left ventricle acquired in diastole and systole using a Modified Look–Locker Inversion Recovery sequence. Image analysis was performed with a commercially available software package. T1 value was assessed in all 16 myocardial segments and global value was the mean. Results. Table 1 shows the comparison between T1 values calculated from maps obtained in diastole and systole. Systolic T1 values were significantly lower in the basal anterolateral segment, in all medium segments except for the medium inferior segment, and in all apical segments. The percentage difference between diastolic and systolic T1 values was considered to compensate for the higher T1 values in females, and a significantly higher value was detected in females for the majority of medium segments, for all apical segments, and for the global value. Conclusion. The diastolic-systolic discrepancy was more pronounced for the females and at the apical level, supporting the hypothesis that, besides the physiologic variations in myocardial blood volume during the cardiac cycle, the partial volume-effect may be a strong additional contributing factor. Native T1 values should be obtained always in the same cardiac phase to avoid a potential bias in the discrimination between healthy and pathologically affected myocardium.